The impact of managerial ownership, monitoring and accounting standard choice on accrual mispricing - Bernhard Gegenfurtner; Markus Ampenberger; Christoph Kaserer (Technische Universität München, Center for Entrepreneurial and Financial Studies (CEFS), 2009)
We analyse to what extent the accrual anomaly is related to the choice of the accounting system as well as firm-level heterogeneity in corporate governance mechanisms. Using a unique dataset of listed German firms over the period 1995 to 2005 we first corroborate former results indicating that the accrual anomaly is also present in Germany. However, this anomaly seems to be driven mainly by firms with managerial ownership. In a second step, we test how different corporate governance mechanisms affect the anomaly. For the German experiment on voluntary adoption of IFRS our results confirm previous findings that the anomaly is less likely to be present under a conservative accounting system. While creditor monitoring is able to reduce the accrual anomaly, shareholder monitoring is not. Apart from offering evidence related to the cross-sectional difference in the degree of accrual mispricing, our results give also some insights related to the cross-country variation of this phenomenon.
Keywords: G32; G34; M4; M41; 330; Accrual Anomaly; Earnings Quality; Corporate Governance; Managerial Ownership; Capital Market Efficiency; Accounting Standard; Shareholder Monitoring; Creditor Monitoring; Rückstellung; Bilanzpolitik; Corporate Governance; Eigentümerstruktur; International Financial Reporting Standards; Finanzmarkt; Markteffizienz; Kapitalgesellschaft; Deutschland